(untitled) (CIPEEX, 2026)
Systemic arterial hypertension (SAH) is a cardiovascular disease with a high incidence, especially in elderly populations, and is considered a public health problem. Globally, according to the WHO, SAH stands out as the most prevalent chronic noncommunicable disease. When undiagnosed or neglected, it becomes a major risk factor for cardiovascular disease, stroke, kidney failure, and other complications. Given this, the present study aims to address, based on a literature review, Pharmaceutical Care (PC) as a fundamental part of effective treatment of SAH, from prevention to adequate drug control of the disease. By placing the patient at the center of care, PA makes it possible to implement treatment focused on the individual’s specificities, in order to minimize risks through the rational use of drugs, prevention of self-medication, encouragement of treatment adherence, and guidance to seek medical care when necessary. Such actions contribute substantially to the control of SAH and the reduction of associated disease rates, which also results in financial relief for the public health system due to the reduction in the number of hospitalizations.